2019
DOI: 10.1055/s-0041-1730981
|View full text |Cite
|
Sign up to set email alerts
|

Metallosis in Sequelae of Prosthetic Revision for Ceramic Components Fracture: A Case Report with Clinical Presentation Mimicking Periprosthetic Hip Infection

Abstract: Ceramic on ceramic total hip arthroplasties have been developed and widely used during last decades because of their long-term survival and biomechanical properties. One of the most dangerous complication of these implants is the fracture of the ceramic components. The management of this condition should be carefully planned and the choice of the new implant is crucial. We describe a rare case of severe hip synovitis due to massive metallosis in sequelae of mismanaged prosthetic revision for fracture of the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Not only the fact that metallosis requires re‐reoperation but also the possibility of cardiotoxicity due to heavy metal poisoning was the major problem 15 . However, numerous reports indicated that there were no more metallosis‐related events after re‐reoperation with bearing change to CoC or ceramic‐on‐polyethylene 24,26 . In our analysis of extended follow‐up of the previous cohorts, also no subsequent complications were noted in the re‐reoperated patients with metallosis.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Not only the fact that metallosis requires re‐reoperation but also the possibility of cardiotoxicity due to heavy metal poisoning was the major problem 15 . However, numerous reports indicated that there were no more metallosis‐related events after re‐reoperation with bearing change to CoC or ceramic‐on‐polyethylene 24,26 . In our analysis of extended follow‐up of the previous cohorts, also no subsequent complications were noted in the re‐reoperated patients with metallosis.…”
Section: Discussionmentioning
confidence: 57%
“…15 However, numerous reports indicated that there were no more metallosis-related events after re-reoperation with bearing change to CoC or ceramic-on-polyethylene. 24,26 In our analysis of extended follow-up of the previous cohorts, also no subsequent complications were noted in the re-reoperated patients with metallosis. If metallosis was suspected in reoperated patients with MoP bearings after ceramic component fracture, immediate debridement, thorough synovectomy, and bearing change to CoC would prevent subsequent complications and improve the survival of revised implants.…”
Section: Metallosismentioning
confidence: 54%
See 2 more Smart Citations